KAJIAN PENGARUH VARIETAS DAN LOKASI TANAM KELAPA (Cocos nucifera Linn) TERHADAP KUALITAS SANTAN BUBUK - Budianta, Tarsisius Dwi Wibawa; Angriani, Vivi (Widya Mandala Surabaya Catholic University, 2003)
The quality of dry coconut milk was affected by some factors such as coconut maturity, cultivar and location where the coconut planted. This present study investigated the effects of cultivar and planted location on the fat content and fatty acid composition of dry coconut milk. Two planted areas (Kajaran Plantation, Lumajang and Kota Blater Plantation, Jember) and two cultivars (green and yellow) were selected. It was found that dry coconut milk that was produced from Kajaran plantation had a lower fat content than from Kota Blater plantation. Green cultivar in both locations had a lower fat content than yellow cultivar. Fatty acids composition of the yellow cultivar was higher in miristate, oleate and linolete but lower in laurate than the green cultivar. No consistent effect were found on the location factor for the fatty acid composition.